MiR-16 and miR-103 impact 5-HT4 receptor signalling and correlate with symptom profile in irritable bowel syndrome. Issue 1 (December 2017) - Wohlfarth, Carolin; Schmitteckert, Stefanie; Härtle, Janina; Houghton, Lesley; Dweep, Harsh; Fortea, Marina; Assadi, Ghazaleh; Braun, Alexander; Mederer, Tanja; Pöhner, Sarina; Becker, Philip; Fischer, Christine; et al.
Abstract Irritable bowel syndrome (IBS) is a gut-brain disorder involving alterations in intestinal sensitivity and motility. Serotonin 5-HT4 receptors are promising candidates in IBS pathophysiology since they regulate gut motor function and stool consistency, and targeted 5-HT4 R selective drug intervention has been proven beneficial in subgroups of patients. We identified a single nucleotide polymorphism (SNP) (rs201253747) c.*61 T > C within the 5-HT4 receptor geneHTR4 to be predominantly present in diarrhoea-IBS patients (IBS-D). It affects a binding site for the miR-16 family and miR-103/miR-107 within the isoformsHTR4b/i and putatively impairsHTR4 expression. Subsequent miRNA-profiling revealed downregulation of miR-16 and miR-103 in the jejunum of IBS-D patients correlating with symptoms.In vitro assays confirmed expression regulation via three 3′UTR binding sites. The novel isoformHTR4b_2 lacking two of the three miRNA binding sites escapes miR-16/103/107 regulation in SNP carriers. We provide the first evidence thatHTR4 expression is fine-tuned by miRNAs, and that this regulation is impaired either by the SNP c.*61 T > C or by diminished levels of miR-16 and miR-103 suggesting thatHTR4 might be involved in the development of IBS-D.